Skip to main content
Logo image

Section 11.2 The Isomorphism Theorems

Although it is not evident at first, factor groups correspond exactly to homomorphic images, and we can use factor groups to study homomorphisms. We already know that with every group homomorphism ϕ:GH we can associate a normal subgroup of G, kerϕ. The converse is also true; that is, every normal subgroup of a group G gives rise to homomorphism of groups.
Let H be a normal subgroup of G. Define the natural or canonical homomorphism
ϕ:GG/H
ϕ(g)=gH.
This is indeed a homomorphism, since
ϕ(g1g2)=g1g2H=g1Hg2H=ϕ(g1)ϕ(g2).
The kernel of this homomorphism is H. The following theorems describe the relationships between group homomorphisms, normal subgroups, and factor groups.

Proof.

We already know that K is normal in G. Define η:G/Kψ(G) by η(gK)=ψ(g). We first show that η is a well-defined map. If g1K=g2K, then for some kK, g1k=g2; consequently,
η(g1K)=ψ(g1)=ψ(g1)ψ(k)=ψ(g1k)=ψ(g2)=η(g2K).
Thus, η does not depend on the choice of coset representatives and the map η:G/Kψ(G) is uniquely defined since ψ=ηϕ. We must also show that η is a homomorphism. Indeed,
η(g1Kg2K)=η(g1g2K)=ψ(g1g2)=ψ(g1)ψ(g2)=η(g1K)η(g2K).
Clearly, η is onto ψ(G). To show that η is one-to-one, suppose that η(g1K)=η(g2K). Then ψ(g1)=ψ(g2). This implies that ψ(g11g2)=e, or g11g2 is in the kernel of ψ; hence, g11g2K=K; that is, g1K=g2K.
Mathematicians often use diagrams called commutative diagrams to describe such theorems. The following diagram “commutes” since ψ=ηϕ.
A diagram with G mapped with an arrow to H by psi on the top row.  G gets mapped with an arrow down and right to G/K by phi.  G/K gets mapped with an arrow up and right to H by eta.

Example 11.11.

Let G be a cyclic group with generator g. Define a map ϕ:ZG by ngn. This map is a surjective homomorphism since
ϕ(m+n)=gm+n=gmgn=ϕ(m)ϕ(n).
Clearly ϕ is onto. If |g|=m, then gm=e. Hence, kerϕ=mZ and Z/kerϕ=Z/mZG. On the other hand, if the order of g is infinite, then kerϕ=0 and ϕ is an isomorphism of G and Z. Hence, two cyclic groups are isomorphic exactly when they have the same order. Up to isomorphism, the only cyclic groups are Z and Zn.

Proof.

We will first show that HN={hn:hH,nN} is a subgroup of G. Suppose that h1n1,h2n2HN. Since N is normal, (h2)1n1h2N. So
(h1n1)(h2n2)=h1h2((h2)1n1h2)n2
is in HN. The inverse of hnHN is in HN since
(hn)1=n1h1=h1(hn1h1).
Next, we prove that HN is normal in H. Let hH and nHN. Then h1nhH since each element is in H. Also, h1nhN since N is normal in G; therefore, h1nhHN.
Now define a map ϕ from H to HN/N by hhN. The map ϕ is onto, since any coset hnN=hN is the image of h in H. We also know that ϕ is a homomorphism because
ϕ(hh)=hhN=hNhN=ϕ(h)ϕ(h).
By the First Isomorphism Theorem, the image of ϕ is isomorphic to H/kerϕ; that is,
HN/N=ϕ(H)H/kerϕ.
Since
kerϕ={hH:hN}=HN,
HN/N=ϕ(H)H/HN.

Proof.

Let H be a subgroup of G containing N. Since N is normal in H, H/N is a factor group. Let aN and bN be elements of H/N. Then (aN)(b1N)=ab1NH/N; hence, H/N is a subgroup of G/N.
Let S be a subgroup of G/N. This subgroup is a set of cosets of N. If H={gG:gNS}, then for h1,h2H, we have that (h1N)(h2N)=h1h2NS and h11NS. Therefore, H must be a subgroup of G. Clearly, H contains N. Therefore, S=H/N. Consequently, the map HH/N is onto.
Suppose that H1 and H2 are subgroups of G containing N such that H1/N=H2/N. If h1H1, then h1NH1/N. Hence, h1N=h2NH2 for some h2 in H2. However, since N is contained in H2, we know that h1H2 or H1H2. Similarly, H2H1. Since H1=H2, the map HH/N is one-to-one.
Suppose that H is normal in G and N is a subgroup of H. Then it is easy to verify that the map G/NG/H defined by gNgH is a homomorphism. The kernel of this homomorphism is H/N, which proves that H/N is normal in G/N.
Conversely, suppose that H/N is normal in G/N. The homomorphism given by
GG/NG/NH/N
has kernel H. Hence, H must be normal in G.
Notice that in the course of the proof of Theorem 11.13, we have also proved the following theorem.

Example 11.15.

By the Third Isomorphism Theorem,
Z/mZ(Z/mnZ)/(mZ/mnZ).
Since |Z/mnZ|=mn and |Z/mZ|=m, we have |mZ/mnZ|=n.